1990
DOI: 10.1002/bies.950121202
|View full text |Cite
|
Sign up to set email alerts
|

Puffs and gene regulation — molecular insights into the Drosophila ecdysone regulatory hierarchy

Abstract: Sixteen years ago, Michael Ashburner and his colleagues proposed a hierarchical model for the genetic control of polytene chromosome puffing by the steroid hormone ecdysone. The recent molecular isolation and characterization of three early ecdysone-inducible genes has confirmed many aspects of this model--these genes are directly induced by ecdysone, repressed by ecdysone-induced proteins, and appear to encode DNA binding regulatory proteins. The three early genes are also remarkably similar in structure. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 40 publications
1
41
0
Order By: Relevance
“…Thus, we predict that the multiple transcripts encoded by the BR-C and E75 will be expressed in a temporal pattern determined by the lengths of their transcription units and the ecdysone concentrations required for their activation and repression. Consistent with this, both of these early genes contain nested promoters spanning unusually long transcribed regions, up to 100 kb in length (Chao and Guild 1986;Feigl et al 1989;Galcerfin et al 1990;Segraves and Hogness 1990;Thummel 1990). As with E74, the E75 transcripts have distinct temporal responses to a high concentration of ecdysone.…”
Section: Future Considerationsmentioning
confidence: 72%
“…Thus, we predict that the multiple transcripts encoded by the BR-C and E75 will be expressed in a temporal pattern determined by the lengths of their transcription units and the ecdysone concentrations required for their activation and repression. Consistent with this, both of these early genes contain nested promoters spanning unusually long transcribed regions, up to 100 kb in length (Chao and Guild 1986;Feigl et al 1989;Galcerfin et al 1990;Segraves and Hogness 1990;Thummel 1990). As with E74, the E75 transcripts have distinct temporal responses to a high concentration of ecdysone.…”
Section: Future Considerationsmentioning
confidence: 72%
“…Metamorphosis in insects, particularly Drosophila, is also controlled by a member of the nuclear receptor family, the ecdysone receptor. Extensive genetic and molecular analyses have demonstrated that a complex gene regulation cascade regulates the metamorphic transformations and the existence of feedback mechanisms involving transcription factors encoded by ecdysone target genes (96,97). Such feedbacks appear also to exist during amphibian metamorphosis as a recent study has shown that a TH-induced transcription factor can bind to the TH-dependent promoter of the X. laevis TRbA genes to regulate TRb expression (98).…”
Section: Discussionmentioning
confidence: 99%
“…These polytene puffs are cytologically visible structures that appear and recede in a temporal pattern that reflects increased and decreased transcription, respectively, of loci within the puffs (for review, see Thummel 1990). Previous studies demonstrated that Pol IIo localizes to puffs (Weeks et al 1993).…”
Section: Spt5 and Spt6 Colocalize With Pol Iio On Drosophila Polytenementioning
confidence: 99%